Factors Affecting the Success of the National Tuberculosis Control Program in Hospitals in Indonesia Based on the National Hospital Accreditation Standards (SNARS): A Scoping Review - Figi Bayu Joko Saputro; Farid Agushybana; Sutopo Patria Jati (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Tuberculosis (TB) is an infectious disease that is one of the leading causes of health problems worldwide and in developing countries. Hospitals have a very important role in the success of Tuberculosis control programs. Tuberculosis prevention and control encompass a range of health initiatives that are designed to safeguard public health, mitigate morbidity, disability, and death rates, disrupt the spread of the illness, combat medication resistance, and alleviate the adverse consequences associated with Tuberculosis. This scoping review aims to assess the factors that influence the success of the national tuberculosis control program in hospitals based on the National Hospital Accreditation Standards. A scoping review was conducted in this work, utilizing four databases: Google Scholar, Ebsco, Pro Quest, and Science Direct. The PRISMA Flowchart is a tool used to guide the process of selecting research publications. The inclusion exclusion criteria in the article search were limited to the last 10 years, starting from 2014 to 2023. The results of the scoping review showed that the factors influencing the success of the national tuberculosis program in hospitals based on the National Hospital Accreditation Standards are health promotion, early detection of tuberculosis or health screening, tuberculosis surveillance, risk factor control, surveillance of tuberculosis case finding and treatment, provision of immunity with vaccines and provision of tuberculosis preventive drugs. And in an effort to enhance the effectiveness of the Tuberculosis program, the government, hospitals, and communities should prioritize the implementation of the Directly Observed Treatment Shortcourse program in hospitals to ensure its smooth execution Keywords: Tuberculosis, Hospital, Program